THE UNIQUENESS OF LAGRANGE FUNCTION OF TWO ROTATING BODIES AND FIRST APPROXIMATION METRIC - Abdildin, M. M.; Abishev, M. E.; Beissen, N. A.; Boshkayev, K. A. (Recent Contributions to Physics, 2009)
In this work it is shown that the Lagrange function of two rotating bodies in General Relativity can be obtained, without using Fock’s second method, directly from first approximation metric.